The Cancer Tracking System (CATSystem): Study protocol of a randomized control trial to evaluate a systems level intervention for cervical cancer screening, treatment, referral and follow up in Kenya. - May Maloba; Sarah Finocchario-Kessler; Catherine Wexler; Vincent Staggs; Nicodemus Maosa; Shadrack Babu; Kathy Goggin; David Hutton; Gregory Ganda; Hilary Mabeya; Elise Robertson; Natabhona Mabachi (PLoS ONE)
Background Cervical cancer (CC) is preventable, yet remains a significant public health threat, particularly in Sub-Saharan Africa. Despite considerable awareness, screening rates for CC in Kenya are low and loss to follow-up following treatment for premalignant cervical lesions remains high. This study investigates the efficacy of the Cancer Tracking System (CATSystem), a web-based intervention, to improve CC screening and treatment retention. Methods A matched, cluster randomized controlled trial will be conducted in Kenyan government hospitals (n = 10) with five intervention and five standard-of-care (SOC) sites. The primary outcome is the proportion of women with a positive screen who receive appropriate treatment (onsite or referral). Secondary outcomes include CC screening uptake among all women and timeliness of treatment initiation. We will utilize mixed methods to assess intervention feasibility, acceptability, and cost-effectiveness. Discussion The CATSystem has the potential to improve CC care in Kenya by leveraging existing technology to address known barriers in the screening and treatment cascade. This study will provide valuable evidence for potential scale-up of the intervention.